Development of Functional Chicken Chips using Flaxseed and Oats Powder - Kasthuri, S.; Mandal, P.K.; Pal , U.K. (Journal of Meat Science, 2016)
Consumption of unhealthy snack foods with high fat content, added chemical preservatives and low nutritive value is one of the predisposing factors for most of the lifestyle diseases. So, there is need for development of ready-to eat shelf stable functional meat chips. This study was undertaken to standardize the recipe and procedure for preparation of chicken chips. Chicken chips recipe and procedure were standardized and three cooking methods viz. deep fat frying, microwave cooking and hot air oven cooking were compared. Sensory scores for appearance, flavour, texture, crispiness and acceptability were significantly (p<0.05) higher for the product prepared by microwave cooking. Hence, microwave cooking was selected for the preparation of chicken chips. To develop functional chicken chips different levels (2, 4 and 6%) of flaxseed powder (FSP) and (3, 6 and 9%) oats powder (OP) were added in to the standardized recipe. Chicken chips containing 4% FSP and 6% OP had scores of 6.37 and 6.47 for appearance; 6.70 and 6.70 for flavour; 6.70 and 6.50 for texture; 7.0 and 6.83 for crispiness; 6.83 and 6.60 for acceptance, respectively on 8 point hedonic scale. Based on sensory quality FSP level of 4% and OP 6% were selected for incorporation into chicken chips recipe for the development of functional chicken chips (FCC).